Release of fatty acid amides in a patient with hemispheric stroke - Schäbitz, Wolf-Rüdiger; Giuffrida, Andrea; Berger, Christian; Aschoff, Alfred; Schwaninger, Markus; Schwab, Stefan; Piomelli, Daniele (Stroke, 2002)
Background: Excitotoxic insults such as stroke may induce release of fatty acid ethanolamides (FAEs), contributing to the downstream events in the ischemic cascade. We therefore studied release of FAEs such as anandamide, palmitylethanolamide (PEA), and oleylethanolamide (OEA) in the brain of a patient suffering from malignant hemispheric infarction treated with hypothermia. Case Description: A patient with life-threatening hemispheric stroke was treated with moderate hypothermia (33°C) that was maintained for 3 days, followed by a 3-day rewarming period. Microdialysis was applied to measure glutamate, lactate, and glycerol by using a microdialysis analyzer. FAEs were measured by microdialysis coupled with high-performance liquid chromatography/mass spectrometry. Release of neuroprotective fatty amides occurred within the first day after ischemia and reached high concentrations for all 3 substances in tissue surrounding the primary ischemic lesion: anandamide up to 42 pmol/mL, PEA up to 120 pmol/mL, and OEA up to 242 pmol/mL. There was a significant correlation with elevation of lactate as early marker for the hypoxic insult. Conclusions: This is the first report demonstrating release of FAEs in vivo during human stroke and may suggest contribution of the FAE signaling system to the pathophysiological events after ischemia.
Gesehen am 01.04.2021